Corruption, Growth, and FDI Spillovers: Evidence from Emerging Market Economies - Firsty Ramadhona Amalia Lubis; Amir Hidayatulloh; Nurul Azizah Az Zakiyyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Countries with substantial increases in economic growth and similar characteristics to developed countries are usually referred to as emerging markets. The problem faced by emerging market countries is the need for more capital investment into the country so that domestic savings are added through efforts to find buy and imports. This study looks at the effect of economic growth, trade openness, control of corruption, and regulatory quality on FDI, specifically in developing countries. The analysis method used the Generalised Method of Moments panel. The data used from 2014-2021 with the analysis areas of Indonesia, Malaysia, the Philippines and Thailand. The results showed that the economic growth variable had a positive and significant effect on FDI, the trade openness variable had a negative and significant effect on FDI, the control of cor-ruption variable had a negative and significant effect on FDI, and the regulatory quality variable had a positive and significant effect on FDI in ASEAN emerging market countries. Keywords: Growth, Trade openness, Control of corruption, and Regulatory quality